Rural finance and agricultural technology adoption in Ethiopia: Does institutional design matter? - Abate, Gashaw T.; Rashid, Shahidur; Borzaga, Carlos; Getnet, Kindie (International Food Policy Research Institute, 2015)
Financial cooperatives and microfinance institutions (MFIs) are the two major sources of rural finance in Ethiopia. Whereas MFIs are relatively new, financial cooperatives have existed for centuries in various forms. The coexistence of two different institutions serving the same group of people, and delivering the same financial services, raises several policy questions. Those questions have become particularly relevant, as the government has embarked on developing a new strategy for improving rural financial services delivery. This study is expected to serve as an input to that policy discussion. Using a unique household survey dataset and the propensity-score-matching technique, we examine the impacts of the two financial service providers on agricultural technology adoption. The results suggest that access to institutional finance has significant positive impacts on both the adoption and extent of technology use.